Impact of Prematurity and Neonatal Complications on the Development of Dyslexia - López-Zamora, Miguel; Porcar Gozalbo, Nadia; López-Chicheri, Isabel; Cano Villagrasa, Alejandro (Wiley, 2025)
Prematurity has been linked to an increased risk of neurodevelopmental disorders, including dyslexia, due to neonatal complications that can impact brain maturation, such as intraventricular haemorrhage, periventricular leukomalacia and respiratory distress syndrome. This study examines the relationship between prematurity, neonatal conditions and dyslexia, using a sample of 120 participants divided into four groups: preterm children with dyslexia (G-PREDIX), preterm children without dyslexia (G-PREMA), full-term children with dyslexia (G-DISLX) and full-term children without dyslexia (G-NODISLX). Key neonatal variables such as gestational age, birth weight, APGAR scores, neonatal complications and NICU admission were analysed in relation to reading performance, assessed through standardized reading tests. Using multiple linear regression models, the study explored whether these early-life factors predict reading difficulties and dyslexia risk. The results indicate that neonatal complications and prematurity alone do not significantly predict dyslexia diagnosis, but a negative trend was observed between intraventricular haemorrhage and periventricular leukomalacia and reading comprehension and word decoding performance. These findings suggest that prematurity, in the absence of other risk factors, does not necessarily result in dyslexia, but when combined with specific neonatal conditions, it may increase the severity of reading difficulties. These results emphasize the importance of early assessment and targeted intervention programs to support the reading development of at-risk preterm children, particularly those with a history of neonatal complications.
Keywords: Dislexia; Lenguaje - Trastornos; Niños prematuros; Lectura - Problemas de aprendizaje; Parto prematuro - Complicaciones y secuelas; dyslexia; language impairment; neonatal complications; premature birth; reading difficulties